2011
DOI: 10.1016/j.neuropharm.2011.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine protects dopamine neurons by a dual action: Reducing activation of microglia and inducing expression of GNDF in astroglia

Abstract: Amantadine is commonly given to alleviate L-DOPA-induced dyskinesia of Parkinson’s disease (PD) patients. Animal and human evidence showed that amantadine may also exert neuroprotection in several neurological disorders. Additionally, it is generally believed that this neuroprotection results from the ability of amantadine to inhibit glutamatergic NMDA receptor. However, several lines of evidence questioned the neuroprotection capacity of NMDA receptor antagonists in animal models of PD. Thus the cellular and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(51 citation statements)
references
References 34 publications
(50 reference statements)
1
48
0
2
Order By: Relevance
“…27,28 Recent studies suggest that amantadine can reduce neuroinflammation induced by lipopolysaccharide in cell cultures or in mice. 8,13 We and others have shown that neuroinflammation may be the underlying pathology for the cognitive impairment after anesthesia and surgery. 11,12 Thus, we proposed that amantadine could reduce cognitive impairments after surgery and designed this study to test this possibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27,28 Recent studies suggest that amantadine can reduce neuroinflammation induced by lipopolysaccharide in cell cultures or in mice. 8,13 We and others have shown that neuroinflammation may be the underlying pathology for the cognitive impairment after anesthesia and surgery. 11,12 Thus, we proposed that amantadine could reduce cognitive impairments after surgery and designed this study to test this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Amantadine has been found to have significant neuroprotective effects. 7,8 One of the mechanisms for these effects as shown in cell culture studies is to enhance the production of glial cell line-derived neurotrophic factor (GDNF). 9 GDNF can inhibit microglial activation and neuroinflammation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amantadine's pleiotropic mechanism makes it a promising anti-depression drug for TBI patients, including: (1) facilitating dopamine release, delaying reabsorption in the presynapse and increasing the number of DA receptors in the post-synapse [58]; (2) uncompetitive NMDA receptor inhibition to regulate the glutamate-induced excitotoxicity [59]; and (3) restraint of the release of proinflammatory factors and stimulation of the production of glial cell-line-derived neurotropic (GDNF) [60]. Amantadine may directly stimulate dopamine release and act as an exogenous dopaminergic supplement to preserve the dopaminergics' concentration in the striatum.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, amantadine 20 mg/kg exhibited antiradical activity by reducing the intensity of lipid peroxidation and increasing glutathione content in the substantia nigra of rats with 6-hydroxydopamine-induced Parkinson's disease [49]. This drug reduced lipopolysaccharide-and 1-methyl-4-phenylpyridinium ion (MPP+)-induced toxicity of dopamine neurons through 1) the inhibition of the release of microglial pro-inflammatory factors, 2) an increase in expression of neurotrophic factors such as GDNF from astroglia [50]. Consequently, the anti-inflammatory properties of amantadine and hemantane contribute to their neuroprotective activity.…”
Section: Discussionmentioning
confidence: 99%